2021
DOI: 10.1007/s13201-021-01412-6
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of potentially toxic elements in surface waters in Ethiopia

Abstract: The Akaki River and its tributaries, in the city of Addis Ababa, are polluted by potentially toxic elements (PTEs) (Sb, Zn, Cd, As, Hg, Cu, Pb, Fe, V, Ni, Co, Mn, Cr, B, Sr and Ba) in varying degrees due to the significantly fast urban expansion and the industrial activities. The water samples collected from twenty-six different locations or sampling sites along the River and some of its tributaries were analyzed by ICP-MS to determine PTEs. The multivariate component analysis was used to evaluate the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The concentrations of Pb, Cr, Mn, Zn, Cu, Sb, B, Fe, and Sr exceeded the permissible limits set in Ethiopian guidelines for drinking water quality (ES, 2001). The concentrations of Cr, Fe, Mn, and Sr were also higher than the United Nations Food and Agriculture Organization (FAO) guideline values for irrigation water (Aschale et al, 2021). The pollution levels of the Akaki River were lowest in sampling sites upstream of the city boundary, where no industry is located close to the rivers, but highest in densely populated and industrial downstream areas, although concentrations declined with distance farther downstream (Aschale et al, 2021).…”
Section: Ecosystem and Human Health Impacts Of Elevated Levels Of Pot...mentioning
confidence: 75%
“…The concentrations of Pb, Cr, Mn, Zn, Cu, Sb, B, Fe, and Sr exceeded the permissible limits set in Ethiopian guidelines for drinking water quality (ES, 2001). The concentrations of Cr, Fe, Mn, and Sr were also higher than the United Nations Food and Agriculture Organization (FAO) guideline values for irrigation water (Aschale et al, 2021). The pollution levels of the Akaki River were lowest in sampling sites upstream of the city boundary, where no industry is located close to the rivers, but highest in densely populated and industrial downstream areas, although concentrations declined with distance farther downstream (Aschale et al, 2021).…”
Section: Ecosystem and Human Health Impacts Of Elevated Levels Of Pot...mentioning
confidence: 75%
“…Literature sources ( Appendix A, Supplementary material ), have indicated that exposure to trace elements as a result of river pollution in the downstream reaches of the Akaki catchment, in Addis Ababa, are higher than upstream reaches. For instance, concentrations of As [37] , [38] , Fe [39] , Cu [37] , [39] , [40] , Mn [37] , [38] , [39] , Zn [37] , [40] , [41] , Cr [37] , [38] , [39] , [42] , Pb [39] , [40] , [41] and Ni [37] , [38] in river and irrigation waters have exhibited this trend in the Akaki catchment. Even though residents in the downstream of Akaki catchment are potentially more exposed to heavy metals, and hence a higher risk of oxidative DNA damage, than those in the upstream, no study has investigated the link between toxic elements and 8-OHdG levels in bio-samples from the residents.…”
Section: Introductionmentioning
confidence: 85%
“…Currently, the Ethiopian tannery industry plays a prominent role in the advancement of the sector in Eastern and Southern Africa [2] . The quality of water bodies in Addis Ababa City has deteriorated, which is ascribed to the large amounts of unrestricted discharge of effluents from industrial, domestic and municipal wastes [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%
“…At the time of this study, 264 m 3 /d of untreated effluent is being discharged to the Fanta River, which is located upstream of Big Akaki River. Big Akaki River is one of the most polluted rivers in Addis Ababa [ 12 , 14 16 ]. There are many reasons for the pollution of this river, among which is the contamination of its tributaries including the Fanta River.…”
Section: Introductionmentioning
confidence: 99%